Pest Identification Guide: An Introduction to Thrips - Nicole Casusa; Hugh Smith (EDIS)
Tiny insects called thrips are difficult to see with the unaided eye but cause very obvious and sometimes ruinous damage to the flowers, buds, and fruit of many important crops. This 2-page guide asks and answers the key thrips questions that allow growers to distinguish between chilli thrips, common blossom thrips, and Western flower thrips to more effectively battle against these destructive pests. What does it look like? What is its life cycle? Where is it found? What type of damage does it cause? And, most importantly, who are its natural enemies? Use this guide to help you identify thrips so that you can take effective steps to control them and limit the damage they cause. Written by Nicole Casuso and Hugh Smith, with photos by Lyle Buss, Jeff Cluever, Vivek Kumar, P.M.J. Ramakers, Gary Vallad, and Hugh Smith. Published by the Entomology and Nematology Department, UF/IFAS Extension, July 2015.